Funding liquidity, bank capital, and lending growth in a developing country - Yen Nguyen; Nguyen Thanh Liem (Cogent Economics & Finance, 2022)
The purpose of this paper is to examine the impacts of funding liquidity and bank capital on lending growth using panel data estimation techniques on a sample of banks in Vietnam from 2005 to 2021. The research shows that funding liquidity and capital have a positive impact on lending growth, confirming the important role of deposits and capital on bank lending activities. There is evidence that capital and funding liquidity can be substitutes to maintain growth in lending, and capital can help address agency problems associated with increased lending. Finally, we perform quantile regression to further investigate whether the above links hold across the distribution of lending growth, and find that the coefficients of funding liquidity, capital and their interaction term remain significant. Based on the research findings, we propose relevant implications for the maintenance of sustainable growth and stability of banks in this market.
Keywords: 330; Bank capital; funding liquidity; lending growth; quantile regression; Vietnam